Common Right Upper Limb Conditions and Treatment Strategies: A Physiotherapy and Occupational Therapy Perspective - alkhaldei, Waleed Jubran; Mohammed, Ammar Abdullah Abdulkarim; Hafiz, Kamil Mustafa Mohammed Kamil; Al Balawi, Abdulrahman Faleh Ateeq; Alturki, Abdalrhman Hussni Yaqub; Al Badani, Azzam Ahmed Mohammed (Journal of Ecohumanism, 2024)
Common Right Upper Limb Conditions and Treatment Strategies: A Physiotherapy and Occupational Therapy Perspective Abstract Introduction: Allied Health Professionals (AHPs) in the NHS often specialize in treating patients with conditions affecting specific anatomical regions. Physiotherapists (PTs) and Occupational Therapists (OTs) working in upper limb specialities have unique AHP perspectives on common conditions and treatment strategies. Purpose: This study explored the common right upper limb conditions and treatment strategies used by PTs and OTs working in upper limb specialities. Method: A qualitative design using semi-structured interviews with PTs and OTs was conducted. Thematic analysis was used to identify themes and sub-themes. Results: Four themes were identified: 1) Common Conditions 2) Treatment Strategies 3) Service Delivery Considerations and 4) Professional Differences. Discussion: Participants frequently treated patients with rotator cuff pathology, nerve entrapments, and post-operative trauma. Exercise was integral across most conditions and professional groupings, although OTs prioritised activities of daily living. This study adds to the understanding of common conditions treated and treatment strategies used by PTs and OTs. Further research is warranted to examine perspectives from other AHPs.